HUBUNGAN RIWAYAT BERAT BADAN LAHIR DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI DESA PARUNGSERAB KECAMATAN SOREANG KABUPATEN BANDUNG (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Introduction: Stunting is malnutrition in toddlers that lasts for a long time and causes inhibition of brain development as well as child development. Stunting is caused by malnutrition in the first 1.000 days of life, from fetus to 24 months of age. Usually indicated by the Z-score of height for age (TB/U) less than – 2 Standard Deviation (SD). The prevalence of stunting in Soreang District is 28 percent and in Parungserab Village is 29 percent. Objective: This study aims to analyze "the relationship birth weight with the incidence of stunting in toddlers aged 24-59 months in Parungserab Village, Soreang District, Bandung Regency". Methods: This type of research is observational analytic with a case control design. The number of research samples was 41 cases and 41 controls selected using simple random sampling. Data were collected using questionnaires and online interviews. Data analysis was performed using the Chi Square test with a significance level of p